Post-cracking deflections of bonded prestressed concrete beams under short-time loads - Karmacharya, Riddhi B.; Pama, Ricardo P.; Cook, David J.; Morino, Shosuke; Canadian Government (Bangkok : Asian Institute of Technology, 1975)
A method of analyzing the post-cracking deflections of prestressed concrete beams under short-time loads is presented. The analysis is based on an elastic-perfectly plastic stress-strain relationship for the concrete and the non-prestressed steel and an elastic-linear strain hardening stress-strain relationship for the prestressing steel. A trilinear moment-curvature curve for a prestressed concrete section is assumed and equations are derived for determining the control coordinates of the curve. This idealized moment-curvature curve is used to predict the deflections of bonded prestressed concrete beams under short-time loads. The prediction of the post-cracking deflections of continuous prestressed concrete beams necessitates the determination of the redundant moments by a trial and err or procedure. The computed values of deflections compares favorably with the existing experimental results. The theoretical values are also compared with the results obtained from the methods suggested by BENNETT and VEERASUBRAMANIAN (1972) and BRANSON (1963).
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Concrete -- Cracking; Prestressed concrete beams; Concrete beams